2022
DOI: 10.1200/op.22.00022
|View full text |Cite
|
Sign up to set email alerts
|

Financial Impact of Medically Integrated Pharmacy Interventions on Oral Oncolytic Prescriptions

Abstract: PURPOSE: As the utilization of oral cancer medications rises, it is vital that cancer centers track costs associated with these expensive medications. This research seeks to report the cost interventions associated with medically integrated pharmacies (MIPs) and mail-order pharmacies. METHODS: Data collection occurred from October 2016 through May 2021. Volunteers input data from their oncology practice into NCODA's Cost Avoidance and Waste Tracker tool, an innovative easy-to use tool that allows practices to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…53 Trained staff can reduce time to initiation of treatment 25,54 and increase adherence rates 26 for patients who were prescribed OAMs; their efforts can lead to significant cost savings for both patients (through financial assistance programs) 55 and health systems (through reduced medication waste). 56 Compared with traditional mail-in pharmacy programs, specialty pharmacies often have staffing and resources to handle payor- and cost-related barriers and disease-specialized pharmacists with expertise on specific OAMs. One specialty pharmacy serving 13 cancer centers developed a centralized assistance resource data set and screened all patients with a co-pay >$100 USD/fill; 22% of prescriptions received some form of assistance for a total benefit of $280,988 USD in 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…53 Trained staff can reduce time to initiation of treatment 25,54 and increase adherence rates 26 for patients who were prescribed OAMs; their efforts can lead to significant cost savings for both patients (through financial assistance programs) 55 and health systems (through reduced medication waste). 56 Compared with traditional mail-in pharmacy programs, specialty pharmacies often have staffing and resources to handle payor- and cost-related barriers and disease-specialized pharmacists with expertise on specific OAMs. One specialty pharmacy serving 13 cancer centers developed a centralized assistance resource data set and screened all patients with a co-pay >$100 USD/fill; 22% of prescriptions received some form of assistance for a total benefit of $280,988 USD in 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…18 Small-scale studies suggested that physician-pharmacy integration is associated with reduced waste. 4 With an on-site pharmacy, physicians can, in principle, switch therapies more quickly if adverse events arise because they can prescribe and dispense therapies for fewer days, thereby preventing waste. If this were the case, however, we should have observed a decrease in mean days' supply among pharmacy-integrated practices as physicians prescribed shorter courses.…”
Section: Discussionmentioning
confidence: 99%
“…3 On-site pharmacies could also avert waste that can occur with mail orders, whose unused supplies must be discarded when a dose is changed or a course of treatment is discontinued. 4,5 On the other hand, if physicians can financially benefit from both oral therapies dispensed at in-house pharmacies and intravenous (IV) therapies, pharmacy integration could lead to increased overall use of both oral and infused therapies as well as high expenditures. Integration could also incentivize the overuse of particularly profitable oral therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that such integrated pharmacies improve patient adherence to oral oncolytics and reduce cost-for example, by checking in with a patient for side effects and toxicity before issuing refills. 2,3 By maintaining a close working relationship with the clinical team, the pharmacy team is able to carry out patient-centric activities such as applying for co-pay assistance programs, charitable grant funding, and manufacturer-provided free drug programs on behalf of patients, which additional studies have shown lead to markedly reduced prescription abandonment rates-compare a reported national average of 18% to <1% abandonment rate, even with comparable rates of financial barriers across populations. 4 Thus, the new interpretation of Stark betrays a somewhat limited understanding of the evolution in medical therapy and practice over the past decade.…”
mentioning
confidence: 99%
“…Data show that quality of care, as measured by time-to-fill, adherence, waste reduction, and toxicity monitoring, is worse when patients are required to use PBM-owned pharmacies, largely because these mail-order pharmacies disrupt the closely coordinated systems that physicians and pharmacists establish to coordinate care for patients. 3,7,8 All four of us are oncologists who often prescribe oral anticancer therapies; we can certainly attest to the lack of a working relationship with pharmacists in the employ of a PBM-operated pharmacy. In fact, we would not know how to even get in touch if we needed closer assistance with a patient.…”
mentioning
confidence: 99%